Developing the Research-Based Field Guides of Insect Pollinators on Tomato Plants - Ermina Tarigan; Syarifuddin Syarifuddin; Ely Djulia (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
To determine: (1) the feasibility and responses of material, learning design, and layout validation experts to the developed research-based field guides of insect pollinators on tomato plants; (2) the responses of the Entomology lecturer to the developed field guides of insect pollinators on tomato plants; and (3) the responses of the Biology/Biology Education students to the research-based field guides of insect pollinators on tomato plants that have been developed. The population was all the Department of Biology students, Universitas Negeri Medan, who took an Entomology course. The sample was taken by random sampling technique with the number of samples for individual groups of 3 students, small groups of 9 students, and limited groups of 21 students. The instruments were the questionnaires of field guides validation as well as students’ responses to the products. The method applied the Thiagarajan 4-D development model, which consists of 4 stages: define, design, develop, and disseminate. However, this study was limited only up to the developmental stage. The results showed that: (1) the field guides were feasible and could be used in learning based on the results of the material, learning design, and layout validation scored 86%, 88%, and 93% (excellent category); (2) the field guides based on the responses of the Entomology lecturer scored 85% (excellent category); and (3) the field guides based on the responses of the students on an individual, small group and limited group tests scored 85.34%, 81.30%, and 83.18% (excellent category), consecutively.